2023
DOI: 10.3389/fpsyg.2023.1146408
|View full text |Cite
|
Sign up to set email alerts
|

Hopelessness and burnout in Italian healthcare workers during COVID-19 pandemic: the mediating role of trait emotional intelligence

Abstract: ObjectiveThe study aims to assess the impact of COVID-19 on healthcare workers’ work-related stress during the first wave of the pandemic in Italy. The main objective is to investigate the existence of a positive correlation between hopelessness and burnout, assuming that burnout may be a risk factor for the development of hopelessness, and to analyze the role that trait Emotional Intelligence (TEI) and changes in workload could have in this relationship. Furthermore, evaluate any significant differences in bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 102 publications
1
4
0
Order By: Relevance
“…Depending on the tool and assessment criteria used, as well as the variables taken into account, such as occupation, high risk or burnout can affect from 12.0% [51] to 61.7% of healthcare workers [18,21,[52][53][54][55][56]. In terms of burnout symptoms, medics primarily experience a psychophysical exhaustion at work, a deterioration in relations with the patient, and a lack of effectiveness, consistent with a study carried out in Italy [57]. Other studies also indicate that the most frequently experienced symptom of burnout is exhaustion [33]; yet, in the study conducted in 2018 among Polish nurses, the lack of involvement in relations with the patients showed the greatest increase, among burnout symptoms, while disappointment rated the lowest [58].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Depending on the tool and assessment criteria used, as well as the variables taken into account, such as occupation, high risk or burnout can affect from 12.0% [51] to 61.7% of healthcare workers [18,21,[52][53][54][55][56]. In terms of burnout symptoms, medics primarily experience a psychophysical exhaustion at work, a deterioration in relations with the patient, and a lack of effectiveness, consistent with a study carried out in Italy [57]. Other studies also indicate that the most frequently experienced symptom of burnout is exhaustion [33]; yet, in the study conducted in 2018 among Polish nurses, the lack of involvement in relations with the patients showed the greatest increase, among burnout symptoms, while disappointment rated the lowest [58].…”
Section: Discussionsupporting
confidence: 77%
“…Many studies show the co-occurrence of burnout and depression [2,20,21,53,66], symptoms of anxiety [61], and even PTSD [66]. In addition, it is estimated that between 5% and 10% of medics experience suicidal thoughts [2,67], and the prevalence of suicide among medics is higher than among the general population [67], especially among nurses [2,57,67].…”
Section: Discussionmentioning
confidence: 99%
“…They hypothesized burnout was an important risk factor for the development of hopelessness which has been associated with other psychological conditions such as depression and suicide. The study reported a significant positive correlation between hopelessness in each burnout dimension ( 4 ). During the pandemic, high stress levels in physicians (30%) were reported by Linzer et al in the USA ( 5 ).…”
Section: Introductionmentioning
confidence: 98%
“…High EI also predicts better academic performance [ 4 , 16 , 17 ] and is associated with lower stress and anxiety levels [ 18 20 ]. Some evidence also indicates that EI could protect against burnout [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%